Sean Lester, Poland and the Nazi takeover of Danzig - McNamara, Paul (2009)
Introduction – Danzig : from Hanseatic Port to Free City, 997-1920 – 'The British period' and the fallout from Locarno, 1920-1929 – The rise of the NSDAP in Danzig and the growth of Gdynia, 1930-1934 – British and Polish appeasement : an overview, 1925-1938 – Lester's appointment as high commissioner – Lester's arrival in Danzig and the realignment of Polish foreign policy – Election fever in the Free City – The political fallout from the 1935 elections – Financial crisis in Danzig, political crisis in Geneva – Bombshell – The calm before the storm – The Leipzig incident – Poland as League mediator – Diplomatic efforts intensify – The political fallout from Lester's 'resignation' – The final humiliation of the League in Danzig – Conclusion